Strategies for Tracing Vocational Training Graduates: Integrating Technology and Industry Needs to Address Labor Market Challenges - RY Kun Haribowo; Anisa Nurpita; Ike Yuli Andjani; Yuni Andari; Sufitri (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2025)
The Competency-Based Training (CBT) program faces several challenges, one of which is its alignment with the needs of the industrial sector. Tracing vocational training graduates is a key factor in measuring the success of training programs and ensuring their relevance to industry demands. This study aims to provide recommendations for effective graduate tracing strategies that can be implemented by vocational training providers. The research employs a mixed-method approach with a descriptive framework, using SWOT analysis and data triangulation techniques. The findings reveal that one of the strengths of graduate tracing at Vocational Training Centers (VTCs) is the high use of social media for interaction among graduates, reported by 89.2% of respondents. On the other hand, a notable weakness is the lack of consistency in implementation, as indicated by 48.1% of VTCs not having a regular schedule for tracking graduates. Changes in labor market demands, increasingly focused on technology-based skills and digitalization, provide opportunities for training providers to adapt their curricula to better align with industry developments. Most BLKs, however, only have 1-2 staff members responsible for graduate tracing, posing a significant challenge. Strategies derived from the Strength-Opportunity quadrant focus on leveraging technology to enhance tracing effectiveness and fostering stronger collaborations with industry. Meanwhile, strategies from the Weakness-Opportunity quadrant emphasize optimizing available resources and enhancing human resource capacity.